Intervensi Program Psikoedukasi Terkait Literasi Kesehatan Mental terhadap Orang Tua - Tri Astria Ningsih Morin; Andi Aulia Saudi; Tarmizi Thalib (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine the effectiveness of psychoeducation in improving mental health literacy among parents of students at SMP X Makassar. The research was conducted on 23 parents of eleventh-grade students at SMP X Makassar. The data collection instrument used was the Mental Health Knowledge Questionnaire (MHKQ) developed by Wang et al. (2013) and adapted by Nur Azizah (2024). This research employed a quantitative approach with a quasi- experimental design, specifically the One-Group Pretest-Posttest design, in which participants were given a pre-test, followed by psychoeducation on mental health literacy, and then a post-test. Data were analyzed using the paired sample t-test to measure the level of effectiveness. The findings showed that psychoeducation was effective in increasing parents’ mental health literacy at SMP X Makassar. The paired sample t-test revealed a significance value of < 0.05, indicating a significant difference between pre-test and post-test scores. Based on the N-Gain analysis, the improvement fell into the “moderately effective” category, demonstrating that psychoeducation contributes positively to parents’ understanding of children’s mental health.